Hybrid turbidite–contourite systems in the modern Tarakan Basin: seismic sedimentology and analogue for subsurface storage - Nugraha, Harya Dwi; Maulin, Hade Bakda (Frontiers in Earth Science, 2025)
Hybrid turbidite–contourite systems are present where gravity-driven and bottom-current processes interact. Although recent studies have advanced our understanding, deciphering the relative roles of downslope and alongslope processes in shaping the deep seafloor remains an important subject of investigation. The Tarakan Basin, offshore northeastern Borneo, is a prolific hydrocarbon province, yet its modern sedimentary systems are poorly understood. Shaped by rapid deltaic sedimentation, active tectonics, and ocean currents–the South China Sea Throughflow (SCSTF) and Indonesian Throughflow (ITF) – the basin offers an ideal setting to study hybrid deepwater processes. Here, we conducted seismic sedimentology analysis to quantify morphometric parameters, delineate seismic facies, and interpret depositional processes using 3D seismic reflection data. Three segments are identified. The Northern Segment is dominated by upslope-migrating sediment waves and plastered drifts, indicative of contourite-dominated conditions. The Central Segment hosts a canyon–drift complex, formed by synchronous interaction of turbidity flows and bottom currents. In contrast, the Southern Segment is shaped mainly by turbidity currents, with gullies and associated sediment waves suggesting limited bottom current influence. These spatial variations reflect a spectrum of hybrid depositional styles, consistent with global models of contourite-, synchronous-, and turbidite-dominated systems. The sedimentary patterns observed provide an analogue for subsurface reservoir and seal distribution, relevant to both petroleum and carbon storage systems.